Study of Chemical Structure and Electrical Properties of Nitrogen-Doped Activated Carbon from Candlenut Shell (Aleurites Moluccana) - Sahrul Hidayat; Sarifah Mudaim; Risdiana - (Universitas Padjadjaran, 2022)
Li-Sulfur batteries have a high theoretical energy density of 1300 Ah/kg which is about 3 times of commercial lithium ion batteries today. It has several problem in application, especially low electrical conductivity (5x10-30 S/cm) and the swelled volume during the charge/discharge process due to the formation of polysulfide. The solution of this problem is binded the Sulfur particles in porous carbon host. Binder Carbon/Sulfur will increase electrical conductivity while preventing swell the volume of Sulfur during the charge/discharge. In this paper, the nitrogen doped of activated carbon from candlenut shell was investigated for host material of carbon. The chemical structure and electrical conductivity of activated carbon doped nitrogen was studied. The synthesis of activated carbon was carried out by the pyrolysis process at 700°C and then activated by impregnation process for 24 hours using KOH as activator. The pyrolysis process is followed by nitrogen doped using NH3 as a source of nitrogen. The weight ratio of carbon and NH3 is 1:3 using 10% and 25% of NH3 concentrations. The sample was then heated in a furnace at 850°C for 3 hours. The results of BET characterization can be determined the surface area of activated carbon from candlenut shell around 681 m2/g. The process of nitrogen doping of activated carbon has been carried out successfully proved by the presence of C-N functional groups through FTIR analysis. Based on the results of SEM-EDX analysis, the nitrogen content in activated carbon is around 0.52% and 0.34% for NH3 concentration of 25% and 10% respectively. The electrical conductivity of nitrogen doped activated carbon is around 2,31 x 102 S/cm and 2,03 x 102 S/cm for NH3 concentration of 25% and 10% respectively.